2013
DOI: 10.1007/s11295-013-0613-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological characterization of chestnut (Castanea sativa Mill.) germplasm in Piedmont (north-western Italy)

Abstract: Castanea sativa Mill. is an important multipurpose tree species for north-western Italy, and specially for Piedmont Region. The preservation of its germplasm from the genetic erosion due to the changes in socio-economic structure of rural areas and specific pathogen attacks is critical. The principal aims of this work were to characterize the chestnut germplasm grown in Piedmont and investigate its genetic structure. Sixty-eight grafted chestnut trees were evaluated using 10 SSRs (simple sequence repeats) loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…and human populations have resulted in the spread of a rich and varied genetic diversity of chestnut throughout most of the world, especially in mountainous and forested regions. Its plasticity and adaptability to different pedoclimates and the wide genetic variability of the species determined the spread of many different ecotypes and varieties in the wild …”
Section: Introductionmentioning
confidence: 99%
“…and human populations have resulted in the spread of a rich and varied genetic diversity of chestnut throughout most of the world, especially in mountainous and forested regions. Its plasticity and adaptability to different pedoclimates and the wide genetic variability of the species determined the spread of many different ecotypes and varieties in the wild …”
Section: Introductionmentioning
confidence: 99%
“…Although microsatellite genotypes of most of the important Galician varieties analyzed in this study have been previously reported by other authors(Pereira-Lorenzo et al 2011), some major varieties such as Negral, Loura, De Presa, and Luguesa and various secondary varieties have not been previously genotyped using SSRs.Comparisons of the values of observed heterozygosis and fixation index obtained in this study with those obtained in other European areas can be made in spite of assayed microsatellites are different; all authors used between 7 and 10 SSRs. The ranking of Ho values in different zones is as follows: Piedmont Ho=0.755>Galicia Ho=0.716>Andalucía Ho=0.727>Emilian Apennines Ho=0.66>El Bierzo (Spain)=0.61>all Iberian Peninsula Ho=0.609(Marinoni et al 2013; Fernández-López and Fernández-Cruz, this document;Martín et al 2009;Berghè et al 2013;Quintana et al 2015; Pereira et al 2011, respectively). The excess of heterozygotes that was detected in this Galician study (F=−0.105) is higher than heterozygosis in varieties of other zones: Emilian Apenin (F=−0.096;Berghè et al 2013); in varieties of Andalucian sweet chestnut orchards (F=−0.058;Martín et al 2009); in Piedmont (F=−0.028;Marinoni et al 2013); in El Bierzo (F=−0.016;Quintana et al 2015); and South Switzerland (F=−0.007;Gobbin et al 2007).…”
mentioning
confidence: 69%
“…The ranking of Ho values in different zones is as follows: Piedmont Ho=0.755>Galicia Ho=0.716>Andalucía Ho=0.727>Emilian Apennines Ho=0.66>El Bierzo (Spain)=0.61>all Iberian Peninsula Ho=0.609(Marinoni et al 2013; Fernández-López and Fernández-Cruz, this document;Martín et al 2009;Berghè et al 2013;Quintana et al 2015; Pereira et al 2011, respectively). The excess of heterozygotes that was detected in this Galician study (F=−0.105) is higher than heterozygosis in varieties of other zones: Emilian Apenin (F=−0.096;Berghè et al 2013); in varieties of Andalucian sweet chestnut orchards (F=−0.058;Martín et al 2009); in Piedmont (F=−0.028;Marinoni et al 2013); in El Bierzo (F=−0.016;Quintana et al 2015); and South Switzerland (F=−0.007;Gobbin et al 2007). …”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Fixation index estimates and AMOVA data are supportive of an unexpectedly high level of genetic differentiation in El Bierzo, larger than that estimated in a previous study with a broader geographical scope. Torello Marinoni et al (2013) revealed that four gene pools contributed to the formation of the population of C. sativa in northwest Italy. Mattioni et al (2013) studied on a largescale the genetic diversity of C. sativa by SSR and the results showed a genetic divergence between the eastern (Greek and Turkish) and western (Italian and Spanish) populations.…”
Section: Introductionmentioning
confidence: 99%